Design and optimization of small scale factory manufacturing system - Lee, Wen Yin (2009)
Investigation on manufacturing system of small scale factory has been carried out in this project. The main manufacturing system focused in this thesis is the factory layout. Poor layout design is determine as a major problem contribution in small scale factory. It will affect the productivity and also line efficiency. Through the study aim is to propose new layout to the factory to improve the productivity and reduce the waste to get more profit so that they can survive even facing competition from bigger factory. This study starts with selection of a suitable factory to be the case study target. After that, visit the factory and identify the problems that occur in the factory layout that affect the productivity of the factory. Get all the data needed and redesign the factory layout to improve productivity of the factory. Simulate the layout using computer aided tools to know the effectiveness of the new layout design. In this study, the application of computer aided tools is Witness software. Two layouts are designed to improve the productivity of the factory. Manual calculation is used to calculate the data get from the factory before insert into software. Mean time and worker efficiency is calculated to improve the accuracy of the simulation result. Productivity and line efficiency of the layout is get from the result to know the performance of the layout. Propose layout 2 can contribute 16.5% increment of productivity compares to original layout and 14.4% of productivity compares to propose layout 1. Propose layout 2 can get higher value of productivity and line efficiency so propose layout 2 is a better layout that can increase the performance of the factory.